Application of tight membrane extraction for amines separation - Salvador Cob, Sara; De Sitter, Kristien; Buekenhoudt, Anita (Frontiers in Chemical Engineering, 2024)
Chiral amines are very valued constituents of many important pharmaceutical compounds and their intermediates. However, the enzymatic production of a chiral amine encounters some challenges, like the use of harsh conditions and the unfavorable thermodynamic equilibrium. In this research the possibilities of tight membrane extraction (ME) for in situ product removal (ISPR)amines separation has been investigated to improve the reaction equilibrium. A specific transaminase reaction was selected for the study in which product amine 1-methyl-3-phenylpropylamine (MPPA) or methyl benzylamine (MBA) needs to be separated from the donor amine isopropylamine (IPA). Tight ME is an innovative separation process in which the membrane is not only an interface, but also a way to add extra selectivity to the process. In the present work, we thoroughly discuss the main factors influencing this novel technique by evaluating the extraction efficiency and extraction rates for the different amines. Then we also determine the optimal parameters for ISPR in enzymatic chiral amine productionthe selected reaction. Supported liquid membrane extraction (SLM), as well as pressure driven filtration, more specifically, nanofiltration (NF), were also studied as benchmark technologies, showing that tight ME has a greater advantage over the two in this specific case, due to the extra affinity factor offered by the membrane. The selectivity of MPPA/IPA in tight ME for the optimized parameters was significantly higher than for SLM and NF.